A Comprehensive Review on Atomic Absorption Spectroscopy: Principles, Techniques, and Applications - Maharani, Eka Putri; Briliana, Hasnaa; Putri, Elisabeth Hanindita; Faraditta, Felicia Stella; Az-zhaffirah, Amalia Rizqi (Jurnal Ilmiah Wahana Pendidikan, 2024)
Atomic Absorption Spectroscopy (AAS) is a chemical analysis equipment that works on the premise of atoms absorbing energy. Atomic spectrometry is a method of measuring spectrum that is related to absorption and atomic emission. Atomic absorption spectrometry (AAS) is a technology that uses free gaseous atoms to absorb electromagnetic radiation at a given wavelength and generate a quantifiable signal. Atomic absorption spectrophotometry is a technique of quantitative elemental evaluation whose size is primarily based totally at the absorption of mild at positive wavelengths via way of means of metallic atoms in a loose state. Atomic absorption spectrophotometry has an instrument that is arguably similar to other types of spectrophotometry but atomic absorption spectrophotometry has a distinctive feature in instrumentation, namely the atomizer. This atomizer will absorb the wavelength directly proportional to Lambert's law. Atomization in atomic absorption spectrophotometry is divided into 3: Atomization with Flame, Vapor Generation Method, Furnace atomization. Interferences in AAS can be categorized into two general groups: spectral and non-spectral. Atomic Absorption Spectroscopy (AAS) stands as a pivotal analytical technique employed across diverse industries, playing a crucial role in the identification and quantification of metallic elements present in a given sample. In the future, AAS could be further developed and improved for applications in various fields.